Institutional Autonomy and Strategic Management in Higher Educational Institutions: Evidence from Nepal - Acharya, Kedar Prasad (Tribhuvan University Journal, 2026)
HEIs play a significant role in economic development and societal transformation, and their effectiveness is closely linked to the extent of academic freedom and institutional autonomy. This study examines the level of academic freedom and autonomy in Nepali HEIs and assesses their influence on strategic formulation, implementation, monitoring, evaluation and control. Data were collected through key informant interviews with HEI officials and a survey of 203 campus chiefs, academic leaders and faculty members. The findings reveal that Nepali universities exercise substantial academic freedom and enjoy considerable autonomy in human resources and organizational domains alongside moderate financial autonomy. However, decision-making authority remains highly centralized at the university’s central office, constraining the operational effectiveness of teaching, learning, research, and extension services to the community. While HEIs demonstrate engagement in strategic planning, they face challenges in articulating clear strategic directions, identifying and evaluating strategic options, executing plans effectively, and conducting monitoring and evaluation. These limitations are further compounded by weak internal governance mechanisms, leadership constraints, limited stakeholder participation, political interference, and inadequate institutional ownership. This study recommends strengthening academic freedom and institutional autonomy with robust accountability mechanisms to enhance responsiveness and innovation. This further emphasizes the need to improve internal governance structures, leadership capacity, participatory practices, and institutional ownership to advance strategic management practices and enhance the quality of teaching, research, and extension services. Overall, this study underscores the critical role of academic freedom and institutional autonomy in enabling HEIs to navigate an increasingly complex and rapidly changing higher-education landscape.